2022
DOI: 10.1186/s12876-022-02188-y
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in laboratory tests predict liver function damage in patients with moderate coronavirus disease 2019: a retrospective multicenter study

Abstract: Background Most patients with coronavirus disease 2019 demonstrate liver function damage. In this study, the laboratory test data of patients with moderate coronavirus disease 2019 were used to establish and evaluate an early prediction model to assess the risk of liver function damage. Methods Clinical data and the first laboratory examination results of 101 patients with moderate coronavirus disease 2019 were collected from four hospitals’ electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Additionally, RBD is positively associated with cardiovascular disease (CVD), type 2 diabetes mellitus (T2DM), and obesity in humans ( Olsen and Blomhoff, 2020 ). In COVID-19 patients, lower serum levels reflect liver function damage (typically associated with prolonged hospitalization) and higher urine levels show up when acute tubular damage occurs associated with proteinuria ( Karras et al, 2021 , Wang et al, 2022 , Fierro, 2020 ). Interestingly, in this study, RBP levels increased with COVID-19 severity mostly in pre-vaccine cohorts, possibly indicating that, regardless nutritional status, patients analyzed presented comorbidities such as CVD, 2DM or obesity, diseases that are associated with worse prognosis and higher mortality in COVID-19 patients ( Cai et al, 2021 , Moghaddam Tabrizi et al, 2021 , Cordero et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, RBD is positively associated with cardiovascular disease (CVD), type 2 diabetes mellitus (T2DM), and obesity in humans ( Olsen and Blomhoff, 2020 ). In COVID-19 patients, lower serum levels reflect liver function damage (typically associated with prolonged hospitalization) and higher urine levels show up when acute tubular damage occurs associated with proteinuria ( Karras et al, 2021 , Wang et al, 2022 , Fierro, 2020 ). Interestingly, in this study, RBP levels increased with COVID-19 severity mostly in pre-vaccine cohorts, possibly indicating that, regardless nutritional status, patients analyzed presented comorbidities such as CVD, 2DM or obesity, diseases that are associated with worse prognosis and higher mortality in COVID-19 patients ( Cai et al, 2021 , Moghaddam Tabrizi et al, 2021 , Cordero et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been contradictory opinions about liver enzymes involvement in mortality and morbidity prediction, as some have discarded the hypothesis that elevation in liver function tests may have any predictive value [ 69 , 73 ], and others proved that elevation over 5 times the upper limit is strongly correlated with high mortality risk [ 39 , 42 , 74 , 75 ]. It was suggested that patients with severe disease might respond more robustly to intensive treatments and prognostic indicators of higher liver enzyme levels [ 76 ].…”
Section: Covid-19 and Liver Chemistrymentioning
confidence: 99%
“…Several prediction models have been proposed in order to estimate the risk of liver injury. For instance, it has been reported that a prediction model incorporating plateletcrit, retinol-binding protein and carbon dioxide combining power could sufficiently predict the occurrence of ALI in patients with moderate COVID-19 in a timely manner[ 165 ]. Another risk scoring system was proposed by Shao et al [ 163 ] with the intention to predict ALI risk, which included three variables upon admission, namely ALT, CRP and lactate dehydrogenase[ 163 ].…”
Section: Predisposing Factors For Alimentioning
confidence: 99%